Berobat Kampung: Religion and Traditional Knowledge of Seeking Recovery in Borneo - Yusdiana, Yusdiana; Hariansyah, Hariansyah; Firmansyah, Dedi; Billia, Dini Presti (Al-Albab, 2023)
This article explores the variants of tradition in seeking recovery within a group of religious community in the upstream Kapuas in Borneo island. It is presented using indigenous psychology, narrative analysis and psycho-anthropology. The data were collected using the techniques of in-depth interviews, psycho-anthropological observations, narrative interpretation and documentation. This work finds that the use of Quranic verses and dhikr as well as religious symbols are are very prominent. The people of the upstream Kapuas river interpret and leave a legacy for traditional healing, beginning with an "agreement", reciting a prayer, enhancing, testing to form and hardening. Passing occurs in a closed, difficult and secret process. The preservation of traditional healing is due to very important facts; that it is low cost, being located far from modern health facilities and short time between risk of death and health resources. In addition, the traditional healers are always ready, providing fast treatment, guaranteed recovery from certain types of diseases. This article suggests that the Sufistic-style traditional healing is profound within the tradition.